2007
DOI: 10.1134/s1068162007020033
|View full text |Cite
|
Sign up to set email alerts
|

Peptide derivatives of tylosin-related macrolides

Abstract: Approaches to the synthesis of model compounds based on the tylosin-related macrolides desmycosin and O-mycaminosyltylonolide were developed using specially designed peptide derivatives of macrolide antibiotics to study the conformation and topography of the nascent peptide chain in the ribosome tunnel. A method for selective bromoacetylation of desmycosin at the hydroxyl group of mycinose was developed, which involves preliminary acetylation of mycaminose. The reaction of the 4"-bromoacetyl derivative of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…OMT was obtained by acidic hydrolysis of tylosin as described earlier . Our strategy of the preparation of OMT peptide derivatives was partially developed in the previous study . In the case of OMT derivatives bearing Trp this approach allowed a relatively simple synthesis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…OMT was obtained by acidic hydrolysis of tylosin as described earlier . Our strategy of the preparation of OMT peptide derivatives was partially developed in the previous study . In the case of OMT derivatives bearing Trp this approach allowed a relatively simple synthesis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation method for the C23 derivatives of OMT, which was developed in our previous research and refined in this study, allowed us to synthesize in satisfactory yields a series of compounds with Trp residues located at different distances from the tylonolide ring. Although no crystal structure of a complex of OMT with the ribosome is available it was conclusively demonstrated that the lactone rings of tylosin and OMT are similarly positioned in NPET .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), thus interfering with peptidyl transferase activity (19,37,38) and resulting in truncated peptides (19). Macrolides with C-5 monosaccharides do not interfere with peptidyl transferase activity but instead block the egress of the nascent peptide from the exit tunnel, leading to peptides up to 8 amino acids long (13,19,27,38,42).…”
Section: Discussionmentioning
confidence: 99%